Effect of Meloidogyne javanica on the growth of pea - Sharma, Ravi Datt; Fonseca, Carlos Eduardo Lazarini da (Pesquisa Agropecuaria Brasileira, 2000)
The root-knot nematode, Meloidogyne javanica commonly causes yield reduction of pea (Pisum sativum L.) in the Federal District of Brazil. The effect of M. javanica on the growth of pea cv. Triofin was studied with five inoculum levels namely 0, 10, 100, 1,000, and 10,000 eggs/kg of soil under greenhouse conditions. There was a progressive decrease in plant growth as the inoculum levels of nematode increased. The rate of nematode multiplication was inversely proportional to the inoculum level. Rhizobial nodulation was adversely affected at all the inoculum levels except for the inoculum level of 10 eggs/kg of soil which showed a 61.63% increase in number of bacterial nodules.